Implantable bio-chip for visible and controllable microwave-induced transcranial acoustic generation - Weian Chao; Ruyi Wen; Yubin Gong; Qiang Liu; Lei Xi (Journal of Innovative Optical Health Sciences)
Ultrasound neuromodulation is a powerful tool for brain investigation and holds great promise for treating brain diseases. However, due to the heterogeneous acoustic properties of skulls, existing ultrasound neuromodulation faces the challenge of severe transcranial acoustic attenuation. To overcome such limitations, we report an implantable bio-chip for visible and controllable microwave-induced transcranial acoustic generation (MI-tAG). The bio-chip is soft, flexible, and biocompatible, with a thickness of 3[Formula: see text]mm, making it suitable for human intracranial implantation. The constituted fluid channels can cover an area of 50[Formula: see text]mm × 60[Formula: see text]mm, enabling widefield neuron stimulation. The particles filled in the fluid channels have both high microwave absorption, ensuring efficient ultrasound generation, and magnetism, allowing noncontact and flexible manipulation by external magnetic fields. The experimental results demonstrate that the optimal MI-tAG can be realized by the combination of particles arranged in a linear pattern and corresponding illumination via a linearly polarized microwave. Stability evaluation indicates that the particles can maintain a consistent acoustic intensity without degradation for at least seven days. The results of in vitro and in vivo experiments show that the MI-tAG can manipulate ultrasound sources and visibly locate them in real time. This study provides a potential innovative approach for future ultrasound neuromodulation, inspiring the development of more useful methods to advance brain research. This study introduces a promising innovative approach for transcranial acoustic generation, potentially inspiring the development of more effective methods for advancing ultrasound neuromodulation.